2011
DOI: 10.1007/s00408-011-9283-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Type Influences the Effectiveness of Pleurodesis in Malignant Effusions

Abstract: Pleurodesis is commonly indicated for symptom relief in patients with malignant pleural effusions. A number of factors may influence pleurodesis outcome, but whether tumor type is one of them is a matter of debate. This study investigates the impact of tumor type on the efficacy of bedside doxycycline and thoracoscopic talc poudrage pleurodesis in order to determine which patients may benefit most from these procedures. A retrospective study of 138 and 450 doxycycline and talc poudrage pleurodesis procedures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 13 publications
1
36
0
4
Order By: Relevance
“…A potential explanation could be that a trapped lung is relatively common in mesothelioma and metastatic tumors of the lung as a result of either visceral pleural restriction (mesothelioma) or endobronchial obstruction (lung cancer). Also, we found that a high tumor burden in the pleural space was negatively associated with the results of pleurodesis [34]. This indicates that the likelihood of achieving a successful pleurodesis decreases with an increasing pleural tumor burden observed during thoracoscopy.…”
Section: Outcome Of Pleurodesis In Different Types Of Tumors In the Pmentioning
confidence: 85%
“…A potential explanation could be that a trapped lung is relatively common in mesothelioma and metastatic tumors of the lung as a result of either visceral pleural restriction (mesothelioma) or endobronchial obstruction (lung cancer). Also, we found that a high tumor burden in the pleural space was negatively associated with the results of pleurodesis [34]. This indicates that the likelihood of achieving a successful pleurodesis decreases with an increasing pleural tumor burden observed during thoracoscopy.…”
Section: Outcome Of Pleurodesis In Different Types Of Tumors In the Pmentioning
confidence: 85%
“…23,24 Studies of talc pleurodesis efficacy focusing specifically on patients with mesothelioma seem to have lower success rates than studies in heterogeneous populations, probably because extensive visceral disease, common in mesothelioma, mitigates against successful pleurodesis because of failure of visceral and parietal pleura apposition combined with a paucity of normal mesothelial cells. 25,26 A retrospective study 27 of 165 patients with malignant pleural mesothelioma who underwent pleurodesis reported that pleural effusion was not controlled in 31% of patients, with no difference between talc slurry and talc poudrage. At the inception of our trial, the predominant method for assessing pleural effusion was chest radiograph-a less sensitive method than ultrasound, which is now widely used.…”
Section: Discussionmentioning
confidence: 99%
“…Pleurodesis with doxycycline or talc may be indicated for symptom relief, as well as serial thoracenteses or even the placement of a PleurX catheter for palliative management in patients who are not suitable for pleurodesis [73,74].…”
Section: Dyspneamentioning
confidence: 99%